Social determinants of mental health among older adolescent girls living in urban informal settlements in Kenya and Nigeria during the COVID-19 pandemic - Alice Mũrage; Anne Ngunjiri; Amy Oyekunle; Julia Smith (Taylor & Francis Group, 2023)
The health burden due to mental health has historically been underestimated with focus on communicable diseases and deaths and little consideration of disability and comorbidity effects of poor mental health. Recent data show increasing trends of mental health disorders as a share of global health burdens and vulnerability of adolescents. This paper aims to explore social determinants of mental health as experienced by adolescent girls, drawing attention to gendered risks during the COVID-19 pandemic. Semi-structured interviews with twenty-two adolescent girls in urban informal settlements in Kenya and Nigeria reveal unique environmental, socio-cultural, economic and educational factors that threatened their mental wellbeing. The pandemic exacerbated these determinants. An equitable recovery will require a consideration of not only disproportional mental health outcomes, but also social determinants that contribute to these outcomes. As more than half of the urban population in sub-Saharan Africa reside in informal settlements, this study has implications for youth-focused mental health interventions in these and similar settings.